Exploring Cognitive Aspects In Lesson Plans Made By Pre - Service Teachers - Purdianata, Galih Razzaq; Siswana , Siswana (Jurnal Locus Penelitian dan Pengabdian, 2025)
Modern education emphasizes the development of critical, analytical, and creative thinking. However, pre-service teachers often prioritize Lower-Order Thinking Skills in their lesson plans, limiting the stimulation of Higher-Order Thinking Skills. This study aims to analyze the use of Operational Verbs in the learning objectives of lesson plans to understand how they reflect cognitive levels and guide the learning process. Using a qualitative content analysis approach, lesson plans created by 6 prospective teachers over 16 sessions were examined through the lens of Bloom’s Taxonomy (C1–C6). Results showed that Lower-Order Thinking Skills dominated (58.33%), especially at C1 (Remembering) and C2 (Understanding), while Higher-Order Thinking Skills accounted for 41.66%, with significant emphasis on C6 (Creating). Cognitive focus varied across individuals, indicating inconsistent application of cognitive depth. These findings underscore the need for more balanced planning and targeted training to strengthen Higher-Order Thinking Skills and meet 21st-century learning demands.